2022
DOI: 10.1371/journal.pstr.0000032
|View full text |Cite
|
Sign up to set email alerts
|

‘Factory farming’? Public perceptions of farm sizes and sustainability in animal farming

Abstract: Farm sizes play an important role in increasing public debates surrounding the sustainability of agriculture, specifically of animal farming. While research cannot find consistent relationships between sustainability and farm sizes, the ‘small-is-beautiful’-hypothesis remains still prominent in public perceptions. The aim of this study is to deeply analyze public associations coming with small and large farms with a focus on sustainability issues, including animal welfare. We additionally consider the memory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A few researchers propose the phaseout of animal agriculture [ 6 ], with some arguing that this is unachievable because it is either unacceptable to the general public, involves powerful and influential interest groups, or too costly to implement [ 284 , 319 , 395 ]. However, as research has shown, the general public are against many of the cruel and inhumane practices used in industrial animal agriculture and the effects that it has on human health, as well as the health of communities and the environment [ [396] , [397] , [398] , [399] ].…”
Section: Discussionmentioning
confidence: 99%
“…A few researchers propose the phaseout of animal agriculture [ 6 ], with some arguing that this is unachievable because it is either unacceptable to the general public, involves powerful and influential interest groups, or too costly to implement [ 284 , 319 , 395 ]. However, as research has shown, the general public are against many of the cruel and inhumane practices used in industrial animal agriculture and the effects that it has on human health, as well as the health of communities and the environment [ [396] , [397] , [398] , [399] ].…”
Section: Discussionmentioning
confidence: 99%